Sample Size for Testing ’White Tip Nematode’ on Paddy Seeds - RAJAN; ARJUN LAL (Seed Research, 2026)
The distribution of white tip nematode Aphelenchoides besseyi on paddy seeds was studied to determine the optimum sample size for seed certification and for quarantine processing of paddy germplasm imported for research purpose. The nematode population on the seeds collected from naturally raised crop was found to be skewed, as the nematodes were concentrated on a 5% seeds mixed with a large number ( 95%) of nematode free seeds. Based on detection levels and statistical analysis for reliability of results, the optimum sample size for certification purpose was found to be 1000 seeds and for quarantine processing, observation of at least 50 seeds is necessary.